Violation of the Principle of Cooperation on Humorous Speech in the Ini Talkshow Event - Astuti, Nia; Zulaeha, Ida (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The private television program presented by Presenter-Comedian Sule and Andre, This Talkshow, is popular with the public because of the presenter's humorous cohesiveness. Violations of the principle of cooperation cause the humorous effect of the language used by the participants based on age, sex, and social status. This research was conducted to analyze the violation of the principle of cooperation in a humorous speech in this talk show using sociopragmatic studies. Sociopragmatics essentially combines two types of studies, namely Sociolinguistics and Pragmatics. Data collection was carried out by a referring method which was continued with skillful in-flight listening techniques and accompanied by recording and recording techniques. Data analysis was performed using the comparing pragmatic method and method of agih. Based on the results of this study, the creation of humorous speeches is carried out by speakers by utilizing violations of the maxims of the principle of cooperation in humorous speech as a source of creativity. Violations of the principle of cooperation often function as supporting humor.